Breaking borders? The European Court of Justice and internal market - Christoph Spengel; Leonie Fischer; Kathrin Stutzenberger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Upon more than 400 judgements on direct taxation, the case law of the European Court of Justice has considerably shaped Member States' tax systems. Based on Member States' tax law adjustments in the context of four landmark rulings on corporate income taxation, we analyse whether case law is a suitable instrument to eliminate tax distortions towards the realisation of a European internal market. Our analysis is based on effective tax burdens using the Devereux/Griffith methodology. Overall, we find that due to Member States' mostly heterogeneous adjustments and varying levels of compliance, cross- border investment continues to be discriminated in some Member States following the Marks & Spencer and National Grid Indus judgements. In addition, differences in the general availability of the rules under scrutiny and design of related provisions, cross-country differences in effective tax burdens and hence distortions to the internal market might persist. We conclude that a comprehensive harmonisation of Member States' tax systems by way of positive integration would be necessary to sustainably eliminate tax obstacles to cross-border business activities.
Keywords: H25; K34; 330; European Court of Justice; Internal Market; Effective Tax Rates; Thin Capitalisation Rules; Cross-Border Loss Relief; Controlled Foreign Company Rules; Exit Taxation